The Will as Conscious Desire: Kuno Fischer between Spinoza and Nietzsche - de Pablos Escalante, Raúl (Anales del Seminario de Historia de la Filosofía, 2016)
It can well be asserted that the volume dedicated to Spinoza in Kuno Fischer’s History of Modern Philosophy is the most important mediation – although not the only one – to comprehend the Spinoza-Nietzsche problem. From his reading in 1881 of this work, Nietzsche recognized Spinoza as a precursor and identified a common tendency between them: “to make knowledge the most potent affect”. The aim of this article is to emphasize Fischer’s exposition of some of the contents of Spinoza’s philosophy to better grasp its influence on Nietzsche and to highlight the importance of this forgotten classic in the history of philosophy. Specifically, chapter 22 from the 1865 edition – titled “The human will” – shall be considered, where will is construed as conscious desire. This has important consequences on Nietzsche’s reception of Spinozian philosophy. Moreover, it can also allow a much richer discussion of the not always pondered role of will in Spinoza.